Endoscopic Endonasal Resection of Symptomatic Rathke Cleft Cysts: Total Resection or Partial Resection - Zhang, Xiejun; Yang, Jihu; Huang, Yan; Liu, Yufei; Chen, Lei; Chen, Fanfan; Huang, Guodong (Frontiers in Neurology, 2021)
Objective: Rathke cleft cysts (RCC) are benign sellar lesions, and endoscopic endonasal surgery (EES) for symptomatic RCC is becoming increasingly popular, but total resection or partial resection (TR or PR) of the cyst wall is still inconclusive. The aim of this study was to review the complications and clinical prognoses associated with total and partial resection of the cyst wall by EES. Methods: We retrospectively analyzed a series of 72 patients with symptomatic RCC treated by EES from -January 2011 to June 2019 at Shenzhen University First Affiliated Hospital. For these 72 cases, 30 were treated with TR and 42 were treated with PR. Intra- and post-operative complications and clinical prognosis were investigated. Results: All 72 patients underwent a pure EES. In the TR group, 10 patients (33.3%) had intraoperative cerebrospinal fluid leakage (CSF leak), three patients (10%) had postoperative CSF leak, eight patients (26.7%) had postoperative diabetes insipidus (DI), eight patients (26.7%) had postoperative electrolyte disturbance, and 12 patients (40%) had temporary hypopituitarism postoperatively. While in the PR group, three patients (7.1%) had intraoperative CSF leak, two patients (4.8%) had postoperative DI, three patients (7.1%) had postoperative electrolyte disturbance, four patients (9.5%) had temporary hypopituitarism postoperatively, and no cases experienced postoperative CSF leak. The intra- and post-operative complications were significantly higher in TR group then PR group (P IntraoperativeCSFleak = 0.004, P Post−operativeCSFleak =0.036, P TransientDI = 0.008, P Temporaryhypopituitarism = 0.002, P Permanenthypopituitarism = 0.036, P Electrolytedisturbance = 0.023). No significant differences in post-operative improvement and recurrence. Conclusions: EES is a safe and effective approach for the treatment of symptomatic RCC. Complete sucking out the cyst contents and partial resection of the cyst wall may be sufficient for treatment, and total resection of the cyst wall is associated with a higher incidence of complications.